(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
This article reflects about the registration of different traditional puppet theatre manifestations as intangible cultural heritage. It discusses how important it is to preserve traditional puppetry but also presents doubts about how the registration affects this art form that is constantly changing. Keywords: Cultural heritage. Puppet theatre. Traditional puppet theatre.